P-C4 Associating HIV-1 Env trimer structures with functional Env conformational states by smFRET analysis. (April 2018) - Lu, Maolin; Ma, Xiaochu; Castillo-Menendez, Luis; Gorman, Jason; Munro, James; Kwong, Peter; Blanchard, Scott; Sodroski, Joseph; Mothes, Walther
Abstract : The HIV-1 envelope glycoprotein (Env) trimer mainly exists in a closed conformation (state 1), which is driven by CD4 binding through an intermediate conformation (state 2) to the open CD4-bound conformation (state 3). These functional Env states can be visualized by single-molecule Fluorescence Resonance Energy Transfer (smFRET). A breakthrough in the structural characterization of the HIV-1 Env trimer has been the generation of recombinant cleaved soluble gp140 SOSIP.664 trimers. Parallel cryoelectron microscopy studies have been performed with the mature HIV-1JR-FL Env in complex with the PGT151 neutralizing antibody. Both approaches resulted in similar structures. It is currently generally assumed that these structures represent the ground state of HIV-1 Env (state 1). Here we apply smFRET to probe the conformational state of HIV-1 Env in these constructs and antibody complexes. Fluorophores were introduced at the identical positions in the HIV-1 Env proteins used for structural studies and the native Env on the surface of virions, and the resulting smFRET values compared. Surprisingly, smFRET data reveal that both the soluble gp140 SOSIP.664 and PGT151-HIV-1JR-FL Env structures correspond to the state 2 gp120 conformation observed on the virus. Our data suggest that the all-important structure of state 1 of HIV-1 Env, which is the target of the majority of broadly neutralizing antibodies, remains unknown. Determining the structure of this additional conformation observed on native virions should allow the design of second generation immunogens that specifically present the state 1 conformation of HIV-1 Env.